The Overlooked turning point in history - Perat, Zvonko (Šolsko polje, 2012)
The main focus in this paper is on the current state of the first and the second period (from the 1st to the 6th class) of Slovene primary schools. The emphasis is placed on the state of literacy on the first stage of compulsory education. A detailed description of the path leading to the current situation as well as the results of the research on the gifted and talented pupils, conducted by Benjamin Jurman (a researcher at the National Education Institute in Ljubljana) with a proposed solution to the current quandaries will be also presented. Slovenia became independent on 25th June 1991, but we still cannot get rid of the fifty-year long mentality based on self-managing socialism. If Wittgensteinćs points of view are distorted a little bit, we can see that a certain conceptuality (method) has overshadowed the others. That is why all the methods have to be reviewed again - those neglected, as well as the privileged ones in order to find the forgotten paths to literacy, which is unfortunately in decline. This sad stage was achieved in just one decade (1945 - 1955) with the establishment of a unique model of the school of workers, farmers and honest intelligentsia and by implementing three socialist school reforms (1955 - 1991). With today's Slovene school reform, we just keep on this bleak path. We have a democratic nation - state, so no actions can be imposed by anybody upon ourselves. If we want to be in line with the famous revolutionary song chorus: "we will take freedom by ourselves", we have to accept the weight of freedom and consequently we ought to take responsibility for our actions as well. For the first time in history, we are responsible for our national education. However, it seems that this opportunity has not yet been seized.
Keywords: literacy process; osnovne šole; razredni pouk; school reforms; pedagogy of culture; opismenjevanje; pedagogy of capital; šolske reforme; pedagogika kulture; national history; national self-consciousness; demokracija; nacionalna zgodovina; democracy; nacionalno samozavedanje; small nation; vzgoja in izobraževanje; education